2007
DOI: 10.1161/01.str.0000260100.71665.2f
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Stroke in Type 2 Diabetic Patients

Abstract: Background and Purpose-Type 2 diabetes mellitus is a strong predictor of cerebrovascular disease, yet few studies have assessed the incidence of stroke and the role of other risk factors in unselected type 2 diabetes mellitus populations. Methods-We prospectively followed-up 14 432 type 2 diabetes mellitus patients, aged 40 to 97 years, with and without a history of cardiovascular disease at enrollment, and we estimated the incidence of stroke and the hazards ratios with respect to clinical variables. Results-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
76
3
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 33 publications
11
76
3
9
Order By: Relevance
“…In the Framingham study, after the onset of angina, men had a twofold greater risk than women for both myocardial infarction and coronary death after adjustment for age and IHD risk factors (1). We described this sex effect previously in the prevalence (5) and incidence analyses of the first IHD event (12) and stroke (13) in the DAI population. In the present study, on the other hand, the incidence of minor IHD in cohort A was higher in women than in men.…”
Section: Discussionmentioning
confidence: 98%
“…In the Framingham study, after the onset of angina, men had a twofold greater risk than women for both myocardial infarction and coronary death after adjustment for age and IHD risk factors (1). We described this sex effect previously in the prevalence (5) and incidence analyses of the first IHD event (12) and stroke (13) in the DAI population. In the present study, on the other hand, the incidence of minor IHD in cohort A was higher in women than in men.…”
Section: Discussionmentioning
confidence: 98%
“…Evidence suggests that these conditions are associated with an increased frequency of cardiovascular events. Indeed, in the subanalysis of the PROactive study, treatment with pioglitazone was found to be significantly reduce the incidence of secondary stroke by 47% in the type 2 diabetes patients with a previous history of stroke 1) . However, that subanalysis also showed that pioglitazone therapy reduced the incidence of the primary outcome by only 6% (p = 0.350) and did not decrease the incidence of primary stroke (HR = 1.06).…”
Section: (A) Primary Outcomementioning
confidence: 99%
“…According to a 4-year follow-up study, risk factors for stroke in patients with type 2 diabetes include an older age, previous history of cardiovascular disease or stroke and microvascular complications 1) . Carotid artery atherosclerosis is another risk factor for stroke, as well as silent cerebral infarction and carotid artery stenosis 2) , in patients with type 2 diabetes, such that the presence of a common carotid intima-media thickness (IMT) of >1 mm increases the risk of silent cerebral infarction four times compared to its absence 3) .…”
Section: Introductionmentioning
confidence: 99%
“…Cukrzyca jest niezależnym czynnikiem ryzyka udaru niedokrwiennego, powodującym 2,5-3,5-krotny wzrost zapadalności na udar w porównaniu z osobami bez cukrzycy [498,499]. W niniejszym opracowaniu omówienie kwestii udarów mózgu i TIA zostało ograniczone do aspektów związanych z chorobą tętnic szyjnych.…”
Section: Choroba Tętnic Szyjnychunclassified